Photoinduced Antibacterial Activity and Cytotoxicity of CdS Stabilized on Mesoporous Aluminosilicates and Silicates - Anna Stavitskaya; Eliza Sitmukhanova; Adeliya Sayfutdinova; Elnara Khusnetdenova; Kristina Mazurova; Kirill Cherednichenko; Ekaterina Naumenko; Rawil Fakhrullin (MDPI AG, 2022)
Inactivation of bacteria under the influence of visible light in presence of nanostructured materials is an alternative approach to overcome the serious problem of the growing resistance of pathogenic bacteria to antibiotics. Cadmium sulfide quantum dots are superefficient photocatalytic material suitable for visible light transformation. In this work, CdS nanoparticles with size of less than 10 nm (QDs) were synthesized on the surface of natural and synthetic mesoporous aluminosilicates and silicates (halloysite nanotubes, MCM-41, MCM-41/Halloysite, SBA-15). Materials containing 5-7 wt.% of CdS were characterized and tested as agents for photocatalytic bacteria degradation of Gram-positive S. aureus and Gram-negative E. coli with multiple antibiotic resistance. Eukaryotic cell viability tests were also conducted on the model cancer cells A 459. We found that the carrier affects prokaryotic and eukaryotic toxicity of CdS quantum dots. CdS/MCM-41/HNTs were assumed to be less toxic to eukaryotic cells and possess the most prominent photocatalytic antibacterial efficiency. Under visible light irradiation, it induced 100% bacterial growth inhibition at the concentration of 125 μg/mL and the bacteriostatic effect at the concentration of 63 μg/mL. CdS/MCM-41/HNTs showed 100% E. coli growth inhibition in the concentration of 1000 μg/mL under visible light irradiation.